Bromodomain inhibitor OTX015 in patients with acute leukaemia: a dose-escalation, phase 1 study. Issue 4 (April 2016) - Berthon, Céline; Raffoux, Emmanuel; Thomas, Xavier; Vey, Norbert; Gomez-Roca, Carlos; Yee, Karen; Taussig, David Christopher; Rezai, Keyvan; Roumier, Christophe; Herait, Patrice; Kahatt, Carmen; Quesnel, Bruno; et al.
Summary: Background: Bromodomain and extraterminal (BET) proteins are chromatin readers that preferentially affect the transcription of genes with super-enhancers, including oncogenes. BET proteins bind acetylated histone tails via their bromodomain, bringing the elongation complex to the promoter region. OTX015 (MK-8628) specifically binds to BRD2, BRD3, and BRD4, preventing BET proteins from binding to the chromatin, thus inhibiting gene transcription. OTX015 inhibits proliferation in many haematological malignancy cell lines and patient cells, in vitro and in vivo. We aimed to establish the recommended dose of OTX015 in patients with haematological malignancies. We report the results of patients with acute leukaemia (leukaemia cohort). Methods: In this dose-escalation, phase 1 study we recruited patients from seven university hospital centres (in France [five], UK [one], and Canada [one]). Adults with acute leukaemia who had failed or had a contraindication to standard therapies were eligible to participate. OTX015 was given orally at increasing doses from 10 mg/day to 160 mg/day (14 of 21 days), using a conventional 3 + 3 design. In this open-label trial, OTX015 was initially administered once a day, with allowance for exploration of other schedules. The primary endpoint was dose-limiting toxicity (DLT), assessed during the first treatment cycle (21 days). The study is ongoing and is registered withClinicalTrials.gov, NCT01713582 . Findings: Between Jan 18, 2013, and Sept 9, 2014, 41 patients, 36 with acute myeloid leukaemia, a median age of 70 years (IQR 60–75) and two lines of previous therapy, were recruited and treated across six dose levels of OTX015. No DLT was recorded until 160 mg/day, when one patient had grade 3 diarrhoea and another had grade 3 fatigue. However, concomitant grade 1–2 non-DLT toxic effects (ie, gastrointestinal, fatigue, or cutaneous) from 120 mg doses hampered patient compliance and 80 mg once a day was judged the recommended dose with a 14 days on, 7 days off schedule. Common toxic effects for all OTX015 doses were fatigue (including grade 3 in three patients) and bilirubin concentration increases (including grade 3–4 in two patients). OTX015 plasma exposure increased proportionally up to 120 mg/day with trough concentrations in the in-vitro active range from 80 mg/day (274 nmol/L). Three patients (receiving 40 mg/day, 80 mg/day, and 160 mg/day) achieved complete remission or complete remission with incomplete recovery of platelets lasting 2–5 months, and two additional patients had partial blast clearance. No predictive biomarkers for response have been identified so far. Interpretation: The once-daily recommended dose for oral, single agent oral OTX015 use in patients with acute leukaemia for further phase 2 studies is 80 mg on a 14 days on, 7 days off schedule. Funding: Oncoethix GmbH, a wholly owned subsidiary of Merck Sharp & Dohme Corp.